DEFOLIADORES DE ENCINAR EN EL ANDÉVALO OCCIDENTAL DE LA PROVINCIA DE HUELVA. COMPARACIÓN ENTRE DOS SITUACIONES PUNTUALES: EL PERIODO 1985-1988 Y EL AÑO 2000 (III Congreso Forestal Español, 2001)
The great economic and ecological importance of holm oak (Quercus ilex L.) in Spain makes necessary to study the presence and repercussion of leaf-damaging insects in holm oak forests. The field study has been carried out in “Los Millares”, one property of Andévalo Occidental (southern Spain, Andalusia, Huelva). This zone was chosen for two reasons: the existence of previous data about the presence and evolution of leaf-damaging insects during the period 1985-1988, fruit of the work of F.J. Toimil and collaborators; as well as the certainty that this year the population of this insects was very high. The results showed that Tortrix viridana, Archips xylosteana, Periclista andrei and, on a smaller scale, Catocala nynphagoga y Dryobotodes eremita constitute at the moment the main leaf-damaging insects, representing more than 87% of the leaf-damaging found. This population can cause big damages in the holm oak forests, with important economic and ecological losses